2007
DOI: 10.1159/000101403
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Do Not Enhance the Trans-Basement Membrane Migration of Neutrophils

Abstract: Background: There is increasing evidence that both neutrophilic and eosinophilic inflammation persist in the airways of patients with severe asthma. We have reported a positive relationship between the concentrations of eosinophils and neutrophils in sputum from severe asthmatics, suggesting a possible role of eosinophils in regulating neutrophilic inflammation. The aim of this study was to investigate whether activated eosinophils modify the trans-basement membrane migration (TBM) of neutrophils. Methods: Eos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This sequence of events is thought to enhance inflammation. A recent study has reported neutrophil migration by IL-8 possibly leads to eosinophilia in severe asthma (Kobayashi et al, 2007). In this study, IL-8 production by eosinophils increased by 10% due to DEPs exposure.…”
Section: Discussionsupporting
confidence: 53%
“…This sequence of events is thought to enhance inflammation. A recent study has reported neutrophil migration by IL-8 possibly leads to eosinophilia in severe asthma (Kobayashi et al, 2007). In this study, IL-8 production by eosinophils increased by 10% due to DEPs exposure.…”
Section: Discussionsupporting
confidence: 53%
“…It is possible that lower concentrations of GM-CSF are needed for an antiapoptotic effect on eosinophils than on neutrophils: 100 pg/mL vs 100 ng/mL, respectively. 18 38 Thus, in eosinophilic asthma where the eosinophil but not neutrophil numbers are high, the levels of GM-CSF in the lungs and airways may be very low (pg/mL) but still effective on eosinophils, and these low GM-CSF levels might have been neutralised at 400 mg dosing of KB003. Conversely, in neutrophilic asthma, where antiapoptosis of neutrophils may be important, the GM-CSF levels in lungs/airways required for such an effect may have to be higher (ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…As those with asthma with the EOS hi /NEU hi pattern were more often treated with ICS, the high eosinophil and neutrophil counts could be at least partially a consequence of steroid treatment, known to enhance neutrophil survival 28. Neutrophils may lead eosinophils to accumulate in the airways of patients with severe asthma and possibly aggravate the disease,29 and it is unlikely that eosinophils regulate neutrophilic inflammation 30. High eosinophil and neutrophil counts may also be related to exposure to specific environmental factors, in particular ozone, recently found to promote an antiapoptotic environment in allergen-primed animals 31.…”
Section: Discussionmentioning
confidence: 99%